Answer:
10
Step-by-step explanation:
First convert the fractions.
9 1/6 to 55/6 and 1 1/11 to 12/11
With these fractions, you can cross out 11 and 6.
55 times 12 5 × 2
6 11 1 × 1
This equals 10/1 or 10
Final answer:
To multiply 9 1/6 by 1 1/11, first convert them to improper fractions, 55/6 and 12/11 respectively. Multiply the numerators together to get 660, and the denominators together to get 66. Simplify by dividing both by their greatest common divisor, which is 66, to get the simplest form, which is 10.
Explanation:
The question asks to multiply 9 1/6 by 1 1/11 and express the answer in simplest form. First, we will convert these mixed numbers to improper fractions. For the first number, 9 1/6, we multiply the whole number part by the denominator of the fractional part and add the numerator: (9 × 6) + 1 = 54 + 1 = 55, thus we get 55/6. For the second number, 1 1/11, we follow the same process: (1 × 11) + 1 = 11 + 1 = 12, resulting in 12/11.
Next, we multiply the resulting improper fractions. The numerators are multiplied together, and the denominators are multiplied together yielding 55 × 12 over 6 × 11 which equals 660/66. Simplifying by common factors, we notice that both the numerator and denominator have a common factor of 66. Dividing the numerator and denominator by 66 gives us the simplest form, which is 10/1 or simply 10.
A bird is flying at a height of 2 meters above the sea level. The angle of depression from the bird to the fish it sees on the surface of the ocean is 15∘. Find the distance the bird must fly to be directly above the fish. Round to the nearest ten
See the attached picture:
The function f(x) = 4x + 5,000 represents the amount of money a television is being sold for, where x is the number of televisions being manufactured.
The function g(x) = 20x − 500 represents the cost of production, where x is the number of televisions being manufactured.
What is (f − g)(100)? Explain.
a. $6.9K is the profit made from 100 TVs
b. $3.9K is the profit made from 100 TVs
c. $6.9K is the cost of manufacturing 100 TVs
d. $3.9K is the cost of manufacturing 100 TVs
Answer:
The opción b
Step-by-step explanation:
the profit is defined by
[tex]Profit=Gain-cost[/tex]
In this case [tex](F-g)(100)=[/tex] is the profit to sell 100 television and is calculated
[tex]F(x)-g(x)=4x+5000-(20x-500)=4x-20x+5000+500=-16x+5500=-16*(100)+5500=3900[/tex]
[tex]3900=3.9k[/tex]
Answer:
The answer You're looking for is B)$3.9K is the profit from 100 TV's
Step-by-step explanation:
Find four distinct complex numbers (which are neither purely imaginary nor purely real) such that each has an absolute value of 3.
Answer:
0.5 + 2.985i1 + 2.828i1.5 + 2.598i2 + 2.236iExplanation:
Complex numbers have the general form a + bi, where a is the real part and b is the imaginary part.
Since, the numbers are neither purely imaginary nor purely real a ≠ 0 and b ≠ 0.
The absolute value of a complex number is its distance to the origin (0,0), so you use Pythagorean theorem to calculate the absolute value. Calling it |C|, that is:
[tex]|C| = \sqrt{a^2+b^2}[/tex]Then, the work consists in finding pairs (a,b) for which:
[tex]\sqrt{a^2+b^2}=3[/tex]You can do it by setting any arbitrary value less than 3 to a or b and solving for the other:
[tex]\sqrt{a^2+b^2}=3\\ \\ a^2+b^2=3^2\\ \\ a^2=9-b^2\\ \\ a=\sqrt{9-b^2}[/tex]
I will use b =0.5, b = 1, b = 1.5, b = 2
[tex]b=0.5;a=\sqrt{9-0.5^2}=2.958\\ \\b=1;a=\sqrt{9-1^2}=2.828\\ \\b=1.5;a=\sqrt{9-1.5^2}=2.598\\ \\b=2;a=\sqrt{9-2^2}=2.236[/tex]
Then, four distinct complex numbers that have an absolute value of 3 are:
0.5 + 2.985i1 + 2.828i1.5 + 2.598i2 + 2.236iinput x 2,4,6,8 output y 1, 2, 3, 4 compare the table with the relation f(x) =3x-10. Which relation has a greater value when x= 8
Answer:
The function f(x)=3x-10 has the greater value at x=8.
Step-by-step explanation:
In the table, x=8 corresponds to y=4.
In the function f(x)=3x-10 when x=8, y corresponds to f(8)=3(8)-10=24-10=14.
SInce 14>4 , the the function f(x)=3x-10 has a greater value at x=8 than the table does.
Analyze the diagram below and complete the instructions that follow. Name one pair of nonadjacent complementary angles in the diagram.
Answer:
The answer is FEG and EGF
The pair of angles, FEG and FGE, are nonadjacent and complementary, which means their sum is 90° but they do not have a common side.
What are complementary and supplementary angles?Two angles are said to be complementary if their sum is 90° and two angles are supplementary if their sum is 180°.
We know two angles are complementary when their sum is 90°, and we also know that two angles are adjacent if they share a common side.
Here we have a pentagon with five sides.
The pair of angles are nonadjacent and complementary meaning their sum is 90° but they do not share a common side they are,
∠FEG and ∠FGE, because ∠FEG + ∠FGE = 55° + 35° = 90°.
learn more about complementary angles here :
https://brainly.com/question/15592900
#SPJ5
How do I solve questions 1,2 and 6?
Answer:
1. P = 13.2542. P = 6.64 + 2x6. P = 10Step-by-step explanation:
[tex]1.\\\text{The length of semicircle:}\\\\l=\dfrac{1}{2}d\pi\\\\d-diameter\\\\d=2.2\\\\\text{substitute:}\\\\l=\dfrac{1}{2}(2.2)\pi=1.1\pi\approx(1.1)(3.14)=3.454\\\\\text{The perimeter of the figure:}\\\\P=2(3.8)+2.2+3.454=13.254[/tex]
[tex]2.\\P=2(3.32)+2x=6.64+2x[/tex]
[tex]6.\\\text{Look at the picture.}\\\\P=4(2)+2(1)=8+2=10[/tex]
Which rule describes the translation below?
Answer: A is correct, (x-5, y-3) Hope this helps, mark brainliest please :)
Step-by-step explanation:
The green triangle is the original, and the blue is the duplicated translation, you know this by the ' mark on the blue S.
You can count the squares from one spot to the next to find how many it moved. It clearly is moved to the left and down though, which means it was subtracted from in both directions.
Answer:A
Step-by-step explanation:
If sin=2/3 and tan is less than 0, what is the value of cos
tangent is less than 0 or tan(θ) < 0, is another way to say tan(θ) is negative, well, that only happens on the II Quadrant and IV Quadrant, where sine and cosine are different signs, so we know θ is on the II or IV Quadrant.
[tex]\bf sin(\theta )=\cfrac{\stackrel{opposite}{2}}{\stackrel{hypotenuse}{3}}\qquad \impliedby \textit{let's find the \underline{adjacent side}} \\\\\\ \textit{using the pythagorean theorem} \\\\ c^2=a^2+b^2\implies \pm\sqrt{c^2-b^2}=a \qquad \begin{cases} c=hypotenuse\\ a=adjacent\\ b=opposite\\ \end{cases}[/tex]
[tex]\bf \pm\sqrt{3^2-2^2}=a\implies \pm\sqrt{5}=a\implies \stackrel{\textit{II Quadrant}}{-\sqrt{5}=a} \\\\[-0.35em] ~\dotfill\\\\ ~\hfill cos(\theta )=\cfrac{\stackrel{adjacent}{-\sqrt{5}}}{\stackrel{hypotenuse}{3}}~\hfill[/tex]
how to solve derivative of (sin3x)/x using first principle
[tex]\dfrac{d}{dx}(\dfrac{\sin(3x)}{x})[/tex]
First we must apply the Quotient rule that states,
[tex](\dfrac{f}{g})'=\dfrac{f'g-g'f}{g^2}[/tex]
This means that our derivative becomes,
[tex]\dfrac{\dfrac{d}{dx}(\sin(3x))x-\dfrac{d}{dx}(x)\sin(3x)}{x^2}[/tex]
Now we need to calculate [tex]\dfrac{d}{dx}(\sin(3x))[/tex] and [tex]\dfrac{d}{dx}(x)[/tex]
[tex]\dfrac{d}{dx}(\sin(3x))=\cos(3x)\cdot3[/tex]
[tex]\dfrac{d}{dx}(x)=1[/tex]
From here the new equation looks like,
[tex]\dfrac{3x\cos(3x)-\sin(3x)}{x^2}[/tex]
And that is the final result.
Hope this helps.
r3t40
Answer:
[tex]\frac{3\cos(3x)}{x}-\frac{\sin(3x)}{x^2}[/tex]
Step-by-step explanation:
If [tex]f(x)=\frac{\sin(3x)}{x}[/tex], then
[tex]f(x+h)=\frac{\sin(3(x+h)}{x+h}=\frac{\sin(3x+3h)}{x+h}[/tex].
To find this all I did was replace old input, x, with new input, x+h.
Now we will need this for our definition of derivative which is:
[tex]f'(x)=\lim_{h \rightarrow 0}\frac{f(x+h)-f(x)}{h}[/tex]
Before we go there I want to expand [tex]sin(3x+3h)[/tex] using the sum identity for sine:
[tex]\sin(a+b)=\sin(a)\cos(b)+\cos(a)\sin(b)[/tex]
[tex]\sin(3x+3h)=\sin(3x)\cos(3h)+\cos(3x)\sin(3h)[/tex]
So we could write f(x+h) as:
[tex]f(x+h)=\frac{\sin(3x)\cos(3h)+\cos(3x)\sin(3h)}{x+h}[/tex].
There are some important trigonometric limits we might need before proceeding with the definition for derivative:
[tex]\lim_{u \rightarrow 0}\frac{\sin(u)}{u}=1[/tex]
[tex]\lim_{u \rightarrow 0}\frac{\cos(u)-1}{u}=0[/tex]
Now let's go to the definition:
[tex]f'(x)=\lim_{h \rightarrow 0}\frac{\frac{\sin(3x)\cos(3h)+\cos(3x)\sin(3h)}{x+h}-\frac{\sin(3x)}{x}}{h}[/tex]
I'm going to clear the mini-fractions by multiplying top and bottom by a common multiple of the denominators which is x(x+h).
[tex]f'(x)=\lim_{h \rightarrow 0}\frac{x(\sin(3x)\cos(3h)+\cos(3x)\sin(3h))-(x+h)\sin(3x)}{x(x+h)h}[/tex]
I'm going to distribute:
[tex]f'(x)=\lim_{h \rightarrow 0}\frac{x\sin(3x)\cos(3h)+x\cos(3x)\sin(3h)-x\sin(3x)-h\sin(3x)}{x(x+h)h}[/tex]
Now I’m going to group xsin(3x)cos(3h) with –xsin(3x) because I see when I factor this I might be able to use the second trigonometric limit I mentioned. That is xsin(3x)cos(3h)-xsin(3x) can be factored as xsin(3x)[cos(3h)-1].
Now the limit I mentioned:
[tex]\lim_{u \rightarrow 0}\frac{\cos(u)-1}{u}=0[/tex]
If I let u=3h then we have:
[tex]\lim_{3h \rightarrow 0}\frac{\cos(3h)-1}{3h}=0[/tex]
If 3h goes to 0, then h goes to 0:
[tex]\lim_{h \rightarrow 0}\frac{\cos(3h)-1}{3h}=0[/tex]
If I multiply both sides by 3 I get:
[tex]\lim_{h \rightarrow 0}\frac{\cos(3h)-1}{h}=0[/tex]
I’m going to apply this definition after I break my limit using the factored form I mentioned for those two terms:
[tex]f'(x)=\lim_{h \rightarrow 0}\frac{x\sin(3x)\cos(3h)-x\sin(3x)+x\cos(3x)\sin(3h)-h\sin(3x)}{x(x+h)h}[/tex]
[tex]f'(x)=\lim_{h \rightarrow 0}\frac{x\sin(3x)(\cos(3h)-1)+x\cos(3x)\sin(3h)-h\sin(3x)}{x(x+h)h}[/tex]
[tex]f'(x)=\lim_{h \rightarrow 0}\frac{x\sin(3x)(\cos(3h)-1)}{x(x+h)h}+\lim_{h \rightarrow 0}\frac{x\cos(3x)\sin(3h)-h\sin(3x)}{x(x+h)h}[/tex]
So the first limit I’m going to write as a product of limits so I can apply the limit I have above:
[tex]f’(x)=\lim_{h \rightarrow 0}\frac{\cos(3h)-1}{h} \cdot \lim_{h \rightarrow 0}\frac{x\sin(3x)}{x(x+h)}+\lim_{h \rightarrow 0}\frac{x\cos(3x)\sin(3h)-h\sin(3x)}{x(x+h)h}[/tex]
The first limit in that product of limits goes to 0 using our limit from above.
The second limit goes to sin(3x)/(x+h) which goes to sin(3x)/x since h goes to 0.
Since both limits exist we are good to proceed with that product.
Let’s look at the second limit given the first limit is 0. This is what we are left with looking at:
[tex]f’(x)=\lim_{h \rightarrow 0}\frac{x\cos(3x)\sin(3h)-h\sin(3x)}{x(x+h)h}[/tex]
I’m going to write this as a sum of limits:
[tex]\lim_{h \rightarrow 0}\frac{x\cos(3x)\sin(3h)}{x(x+h)h}+\lim_{h \rightarrow 0}\frac{-h\sin(3x)}{x(x+h)h}[/tex]
I can cancel out a factor of x in the first limit.
I can cancel out a factor of h in the second limit.
[tex]\lim_{h \rightarrow 0}\frac{\cos(3x)\sin(3h)}{(x+h)h}+\lim_{h \rightarrow 0}\frac{-\sin(3x)}{x(x+h)}[/tex]
Now I can almost use sin(u)/u goes to 1 as u goes to 0 for that first limit after writing it as a product of limits.
The second limit I can go ahead and replace h with 0 since it won’t be over 0.
So this is what we are going to have after writing the first limit as a product of limits and applying h=0 to the second limit:
[tex]\lim_{h \rightarrow 0}\frac{\sin(3h)}{h} \cdot \lim_{h \rightarrow 0}\frac{\cos(3x)}{(x+h)}+\frac{-\sin(3x)}{x(x+0)}[/tex]
Now the first limit in the product I’m going to multiply it by 3/3 so I can apply my limit as sin(u)/u->1 then u goes to 0:
[tex]\lim_{h \rightarrow 0}3\frac{\sin(3h)}{3h} \cdot \lim_{h \rightarrow 0}\frac{\cos(3x)}{(x+h)}+\frac{-\sin(3x)}{x(x)}[/tex]
[tex]3(1) \cdot \lim_{h \rightarrow 0}\frac{\cos(3x)}{(x+h)}+\frac{-\sin(3x)}{x(x)}[/tex]
So we can plug in 0 for that last limit; the result will exist because we do not have over 0 when replacing h with 0.
[tex]3(1)\frac{\cos(3x)}{x}+\frac{-\sin(3x)}{x^2}[/tex]
[tex]\frac{3\cos(3x)}{x}-\frac{\sin(3x)}{x^2}[/tex]
If f(x) = 3x + 2 and
g(x) = 2x- 2,
what is (f - g)(x)?
A. x+4
B. x-2
C. x
D. 5x – 2
E. x-4
Answer:
A. x + 4Step-by-step explanation:
(f - g)(x) = f(x) - g(x)
f(x) = 3x + 2, g(x) = 2x - 2.
Substitute:
(f - g)(x) = (3x + 2) - (2x - 2) = 3x + 2 - 2x - (-2) = 3x + 2 - 2x + 2
combine like terms
(f - g)(x) = (3x - 2x) + (2 + 2) = x + 4
Angie, a student in an advanced statistics course, was given an algebra test and she scored
80%. Is this an accurate predictor of how well students in the algebra class will perform on
the test? (2 points)
Answer:
C. No because Angie is not representative of the population in the algebra class
Step-by-step explanation:
I just took the test and this was correct
No, this is not an accurate predictor
Accurate predictor:Since Angie is the student of an advanced statistics course but she gives the algebra test and scored 80%. We know that the advanced statistics is the higher level of math so it is not an accurate predictor.
An accurate predictor should be applied when the person is 100% confirmed to the related thing. So in the given situation, the student is not 100% confirm.
learn more about test here: https://brainly.com/question/20416466
What is the length of s
5
Step-by-step explanation:
You can use Tan(45)=S/5 to solve for S. Tan basically means Opposite/Adjacent. So the opposite side is S and the adjacent side is S. You plug tan(45) into your calc and then multiply it by 5.
Proportion Below
Tan(45)/1 = S/5
You cross multiply to get Tan(45)*5=S
S would be 5
To check you can use the Pythagorean theorem a^2+b^2=c^2
5^2+5^2=
[tex] {5}^{2} + {5}^{2} = \sqrt{50} [/tex]
25+25=50
Select the correct answer.
What is the equation of the parabola shown in the graph?
Answer:
x=y2/8+y/2+9/2
Step-by-step explanation:
Given:
directrix: x=2
focus = (6,-2)
Standard equation of parabola is given by:
(y - k)2 = 4p (x - h)
where
directrix : x=h-p
focus=(h + p, k)
Now comparing the give value with above:
(h + p, k)= (6,-2)
k=-2
h+p=6
h=6-p
Also
directrix: x=h-p
h-p=2
Putting value of h=6-p in above
6-p-p=2
6-2p=2
-2p=2-6
-2p=-4
p=-4/-2
p=2
Putting p=2 in h-p=2
h=2+p
h=2+2
h=4
Putting k=-2, p=2, h=4 in standard equation of parabola we get:
(y - k)2 = 4p (x - h)
(y-(-2))^2 = 4(2) (x - 4)
(y+2)^2 = 8 (x - 4)
y2+4y+4=8x-32
y2+4y+4+32=8x
x=y2/8+4y/8+36/8
x=y2/8+y/2+9/2!
Which ordered pair is the best estimate for the solution of the system of equations? y=−34x−2y=x+6
Answer:
(-0.23,5.77)
Step-by-step explanation:
The given system of equations is
[tex]y = - 34x - 2...(1)[/tex]
[tex]y = x + 6...(2)[/tex]
We equate both equations to get:
[tex]x + 6 = - 34x - 2[/tex]
Group similar terms to get:
[tex]x + 34x = - 2 - 6[/tex]
[tex]35x = - 8[/tex]
[tex]x = - \frac{8}{35} [/tex]
[tex]x \approx - 0.23[/tex]
Put this value into the second equation to get y
[tex]y = - 0.23 + 6 \approx 5.77[/tex]
(-0.23,5.77)
Pleeaaaase hellllpppp asap
Answer:
Option B
Step-by-step explanation:
the mean is the sum of each value of P(x) multiply for x
Mean= 23x0.16 + 25x0.09 + (26x0.18) + (31x0.12)+ (34x0.24) + (38x0.21)
Mean= 30.47
Answer:
B. 30.47
Step-by-step explanation:
The mean discrete random variable tells us the weighted average of the possible values given of a random variable. It shows the expected average outcome of observations. It's like getting the weighted mean. The expected value of X can be computed using the formula:
[tex]\mu_{x}=x_1p_1+x_2p_2+x_3p_3...+x_kp_k\\\\=\Sigma x_ip_i[/tex]
Using the data given in your problem, just pair up the x and P(x) accordingly and get the sum.
[tex]\mu_{x}=x_1p_1+x_2p_2+x_3p_3+x_4p_4+x_5p_5+x_6p_6\\\\\mu_{x}=(23\times 0.16) + (25\times 0.09) + (26\times 0.18) + (31\times 0.12) + (34\times 0.24) + (38\times 0.21)\\\\\mu_{x} = 30.47[/tex]
Change 50° to radian measure in terms of π.
Answer:
[tex]\frac{5\pi }{18}[/tex]
Step-by-step explanation:
To convert from degree to radian measure
radian measure = degree measure × [tex]\frac{\pi }{180}[/tex]
For 50°, then
radian = 50 × [tex]\frac{\pi }{180}[/tex]
Cancel the 50 and 180 by 10, leaving
radian measure = [tex]\frac{5\pi }{18}[/tex]
the point slope equation of a line is?
Answer:
[tex]\text{The point-slope equation of a line is:}[/tex]
[tex]C.\ y-y_0=m(x-x_0)[/tex]
[tex]m-\text{slope}\\\\(x_0,\ y_0)-\text{point on a line}[/tex]
Which of the following is the simplified form of ^7 radical x • ^7 radical x • ^7 radical x
For this case we must find an expression equivalent to:
[tex]\sqrt [7] {x} * \sqrt [7] {x} * \sqrt [7] {x}[/tex]
By definition of properties of powers and roots we have:
[tex]\sqrt [n] {a ^ m} = a ^ {\frac {m} {n}}[/tex]
So, rewriting the given expression we have:
[tex]x ^ {\frac {1} {7}} * x ^ {\frac {1} {7}} * x ^ {\frac {1} {7}} =[/tex]
To multiply powers of the same base we put the same base and add the exponents:
[tex]x ^ {\frac {1} {7} + \frac {1} {7} + \frac {1} {7}} =\\x ^ {\frac {3} {7}}[/tex]
Answer:
Option 1
Answer: Option 1.
Step-by-step explanation:
We need to remember that:
[tex]\sqrt[n]{a^m}=a^{\frac{m}{n}}[/tex]
Then, having the expression:
[tex]\sqrt[7]{x}*\sqrt[7]{x} *\sqrt[7]{x}[/tex]
We can rewrite it in this form:
[tex]=x^{\frac{1}{7}}*x^{\frac{1}{7}} *x^{\frac{1}{7}}[/tex]
According to the Product of powers property:
[tex](a^m)(a^n)=a^{(m+n)}[/tex]
Then, the simplied form of the given expression, is:
[tex]=x^{(\frac{1}{7}+\frac{1}{7}+\frac{1}{7})}=x^\frac{3}{7}[/tex]
If f of x equals 3x plus 2, find f of 4
Answer:
f(4) = 14
Step-by-step explanation:
f(x) = 3x+2
Let x=4
f(4) = 3(4)+2
= 12+2
= 14
What is the approximate circumference of a circle with a diameter of 9? Round answer to nearest tenth.
The approximate circumference of a circle with a diameter of 9 is 28.3 units, rounded to the nearest tenth, calculated using the formula C = πd.
Explanation:The circumference of a circle can be calculated using the formula C = πd, where C is the circumference and d is the diameter of the circle. Given the diameter of 9, we can substitute this value into the formula to calculate the circumference.
Therefore, the circumference C is:
C = π × 9
Using the approximation for π as 3.14, we get:
C ≈ 3.14 × 9 = 28.26
So, the approximate circumference of the circle is 28.3 units, rounded to the nearest tenth.
a bottle holds 64 fluid ounces of lemonade. How much is this in pints?
Answer:
there are 4 pints
Step-by-step explanation:
64 / 16 = 4
64 fluid ounces of lemonade equals to 4 pints. This is done by dividing the total fluid ounces by the number of fluid ounces in one pint.
Explanation:The question is asking to convert 64 fluid ounces of lemonade into pints. To do this, you should know that 1 pint is equal to 16 fluid ounces. So, you can divide the total fluid ounces by the number of fluid ounces in one pint. In this situation, divide 64 by 16, which equals 4 pints. Therefore, 64 fluid ounces of lemonade equals to 4 pints.
Learn more about conversion here:https://brainly.com/question/34235911
Della’s cats weigh 9.8 and 8.25 pounds,and her dog weighs 25 pounds.How much more does her dog weight than the total weight of both of her cats?
Answer:
6.95 pounds. Her dog weighs 6.95 more pounds than the total weight of both her cats.
Step-by-step explanation:
To find the total weight of her cats, add their weights together:
9.8+8.25
=18.05 pounds
Then to find the difference between the weight of her dog and the weight of her cats' total weight, you subtract the weight of the cats from the weight of the dog:
25-18.05
=6.95 pounds
explain why angle d must be a right angle
Pls help
Answer:
see explanation
Step-by-step explanation:
Using Pythagoras' identity
The square on the hypotenuse of a right triangle is equal to the sum of the squares on the other 2 sides.
Consider the right triangle on the right and calculate n
n² + 2² = 3²
n² + 4 = 9 ( subtract 4 from both sides )
n² = 5 ( take the square root of both sides )
n = [tex]\sqrt{5}[/tex]
If the triangle on the left is right then the square of the longest side must equal the sum of the squares on the other 2 sides.
The longest side is n = [tex]\sqrt{5}[/tex] ⇒ n² = ([tex]\sqrt{5}[/tex] )² = 5 and
([tex]\sqrt{2}[/tex] )² + ([tex]\sqrt{3}[/tex] )² = 2 + 3 = 5
Hence D is a right angle
what is the equation of a line that contains the point (2,-5) and is parallel to the line y=3x-4
Answer:
[tex]\large\boxed{y=3x-11}[/tex]
Step-by-step explanation:
[tex]\text{Let}\\\\k:y=m_1x+b_1\\\\l:y=m_2x+b_2\\\\l\ \perp\ k\iff m_1m_2=-1\to m_2=-\dfrac{1}{m_1}\\\\l\ \parallel\ k\iff m_1=m_2\\\\===================================\\\\y=3x-4\to m_1=3\\\\\text{Therefore}\ m_2=3.\\\\\text{We have the equation:}\ y=3x+b.\\\\\text{Put the coorsdinates of the point (2, -5) to the equation of the line}\\\\-5=3(2)+b\\-5=6+b\qquad\text{subtract 6 from both sides}\\-11=b\to b=-11[/tex]
A spinner has 20 equally sized sections, 8 of which are yellow and 12 of which are blue. The spinner is spun and, at the same time, a fair coin is tossed. What is the probability that the spinner lands on blue and the coin is tails?
Answer:
3/10
Step-by-step explanation:
These two events are independent, so the overall probability is the product of the individual probabilities.
12 blue sections out of 20
p(blue) = 12/20 = 3/5
There is an equal probability of the coin landing on heads or tails.
p(tails) = 1/2
p(blue & tails) = 3/5 * 1/2 = 3/10
Which equation represents the slope-intercept form of the line below? y intercept: 0, 8 slope : 1/2
Answer:
y = 1/2 x + 8
Step-by-step explanation:
We are given the y intercept and the slope, so we can write the equation using the slope intercept form
y = mx+b where m is the slope and b is the y intercept
y = 1/2 x + 8
6. Benjamin has to wear a uniform to school. His uniform is made up of tan or blue pants and a blue or white collared shirt.
Benjamin has 2 pair of blue pants, 2 pair of tan pants, 3 white shirts, and 2 blue shirts. How many combinations can be made
with the clothes Benjamin has to choose from? What is the probability that he will wear his favorite combination, tan pants
and a white shirt?
(SHOW WORK)
Answer:
Probably of getting both = 3/10 *100 = 30%
Step-by-step explanation:
According to the given statement we have four possible combinations:
Blue pants/white shirt, tan pants/white shirt, blue pants/blue shirt, blue pants/white shirt
.probability of getting tan pants = 2/4
probability of getting white shirt = 3/5
probably of getting both = 2/4 x 3/5 = 6/20 = 3/10
probably of getting both = 3/10 *100 = 30% ...
The equation represents Function A, and the graph represents Function B:
Function A
f(x) = x − 9
Function B
graph of line going through ordered pairs negative 1, negative 3 and 2, 3
Which equation best compares the slopes of the two functions?
Slope of Function B = 2 x Slope of Function A
Slope of Function A = Slope of Function B
Slope of Function A = 2 x Slope of Function B
Slope of Function B = − Slope of Function A
Answer:
Slope of Function B = 2 x Slope of Function A
Step-by-step explanation:
step 1
Find the slope of the function A
we have
[tex]f(x)=x-9[/tex]
This is the equation of the line into point slope form
[tex]y=mx+b[/tex]
where m is the slope
b is the y-intercept
therefore
The slope of the function A is
[tex]m=1[/tex]
step 2
Find the slope of the function B
we have the points
(-1,-3) and (2,3)
The slope m is equal to
[tex]m=(3+3)/(2+1)=6/3=2[/tex]
step 3
Compare the slopes
[tex]SlopeA=1\\ SlopeB=2[/tex]
therefore
The slope of the function B is two times the slope of the function A
Answer:
slope of function a = -2
slope of function b = (1 + 5)/(2 + 1) = 6/3 = 2
slope of function b = - slope of function a.
Step-by-step explanation:
PLEASE HELP PLEASE
Which of the following numbers is divisible by 3 and 9?
A. 74,028
B. 40,653
C. 62,997
D. 95,376
Answer:
It's B. 40,653
Step-by-step explanation:
Answer:b
Step-by-step explanation:
Rectangle PQRS has vertices P(1, 4), Q(6, 4), R(6, 1), and S(1, 1). Without graphing, find the new coordinates of the vertices of the rectangle after a reflection over the x-axis and then another reflection over the y-axis.
P(1, 4), Q(6, 4), R(6, 1), and S(1, 1)
New coordinates of the rectangle after a reflection over the x-axis is:
P'(1, -4), Q'(6, -4), R'(6, -1), and S'(1, -1)
New coordinates of the rectangle after a reflection over the y-axis is:
P"(-1, 4), Q"(-6, 4), R"(-6, 1), and S"(-1, 1)
.
Answer:
Over the Y axis.
P(-1, 4), Q(-6, 4), R(-6, 1), and S(-1, 1)
Over the X axis:
P(1, -4), Q(6, -4), R(6, -1), and S(1, -1)
Step-by-step explanation:
In order to finde the new coordinates after a reflection on the Y or X axis, you just have to change the sign of the opposite variable, for example if you want to reflect the points on the Y axis you change the signs of all the X´s on the points, and the same with the reflections of the X axis, you have to change the signs of all the Y´s on the points.